On possibility of creating waveguide sound insulator based on MR material with metal inclusions - Yu. A. Burian; A. V. Zubarev; S. N. Polyakov; S. P. Bobrov (Омский научный вестник)
The problem of reducing the emitted vibrational energy through pipeline systems is relevant. The paper considers the fundamental possibility of constructing a waveguide silencer for pressure pulsations and hydrodynamic noise using MR material (metal rubber) with metal inclusions. The problem of evaluating the sound insulation effectiveness and determining the locking sound waves frequency range is posed and solved. The calculation results show that for metal inclusions in the form of lead balls, the decrease in the pressure pulsation amplitude is 10–20 dB in the frequency range of about 300–1000 Hz and depends on the characteristics of the MR material. It is shown that, if it is possible in principle, a change in the parameters of the wave sound insulator (length, bulk elastic modulus, mass of metal inclusions), the frequency range for blocking sound waves can vary over a fairly wide range.